Building competence through social interaction and the organisational environment: A case study - Disky Rama Mahardika; Leonard Adrie Manafe; Abdul Chamid (Privietlab, 2025)
This study investigates how social interaction and organizational context influence employee performance at PT Chemico Surabaya. Employing a qualitative case study design, this research captures firsthand accounts from workers navigating daily tasks. Data were gathered through in-depth interviews with six respondents, each chosen for their role and active participation in the department’s initiatives. The findings revealed that friendly relations among peers sharply boosted motivation, strengthened teamwork, and cultivated a shared sense of ownership. Similarly, a constructive organizational climate with open leadership, reliable resources, and inclusive practices further uplifts overall output. Together, these insights urge managers to build a culture that prioritizes positive relationships and enabling conditions. This study remains limited by its single-site focus and small sample size, prompting future scholars to extend the inquiry through larger longitudinal studies or cross-firm comparisons.